“Mistura tudo, música, foto, rádio”: a domesticação do telefone celular em um bairro de camadas populares - Silva, Sandra Rubia (Em Questão, 2013)
Ao longo de doze meses de trabalho de campo em um bairro de camadas populares da cidade de Florianópolis (SC) para meu doutorado, pude constatar o crescente consumo de telefones celulares, bem como sua influência na vida social dos membros daquela comunidade. Neste artigo, que tem como norte teórico a atualização do conceito de domesticação – agora aplicado às tecnologias móveis – analiso, através de uma abordagem etnográfica, como o telefone celular vai sendo incorporado, muitas vezes não sem dificuldade, ao cotidiano dos moradores do Morro São Jorge. Além de se dedicar a um tema pouco pesquisado no campo da cibercultura – a apropriação da tecnologia entre as classes populares – o artigo dedica atenção não somente ao consumo de tecnologia entre jovens, mas também entre os idosos. “It mixes up everything, music, pictures, radio”: the domestication of the mobile phone in a low-income neighbourhood” Abstract: During twelve months of fieldwork in a low-income neighbourhood in the city of Florianópolis carried out for my PhD, in the Brazilian Southern state of Santa Catarina, I was able to notice the growing consumption of mobile phones, as well as its influence on the social life of the members of that community. In this paper, which finds its theorethical frame in the updating of the concept of domestication – now applied to mobile technologies – I analyze, through an ethnographic approach, the ways by which mobile phones are appropriated, not without difficulty, to the everyday life of the dwellers of Morro São Jorge. The paper, besides focusing on a theme that has not yet received much attention in the field of cyberculture studies – that is, the appropriation of technology among low-income classes – not only draws attention to the consumption of technology among young people, but also among the elderly.